Randomized Open‐Label Clinical Trial Comparing Prednisolone and Cyclosporine With a Nonrandomized Active Control for Treating Presumed Chronic Pancreatitis in Cats - Yu‐An Wu; Jonathan A. Lidbury; Samiran Sinha; Jörg M. Steiner (Journal of Veterinary Internal Medicine, 2025)
ABSTRACT Background Current management for chronic pancreatitis in cats is largely symptomatic. Anecdotal reports suggest that immunomodulatory treatment can be helpful in some cases, but limited data is available. Objectives Compare the effects of symptomatic treatments alone, an immunosuppressive dosage of prednisolone, or modified cyclosporine on serum feline pancreatic lipase immunoreactivity (fPLI) concentration and clinical activity index (CAI). Animals Forty‐eight client‐owned cats with a presumptive diagnosis of chronic pancreatitis were managed on an outpatient basis. Methods Three‐week randomized open‐label trial with a nonrandomized active control. Owners elected to join either the control or the treatment group; cats enrolled in the treatment group were randomized to receive either prednisolone or cyclosporine. Serum fPLI concentration and clinical signs were recorded at baseline and on Days 10 and 21. Results The average decrease in serum fPLI concentration was 13.0 μg/L (95% CI, −23.9 to −0.9 μg/L) larger for the cyclosporine group (n = 17) than for the control group (n = 16) and 27.6 μg/L (95% CI, −41.2 to −11.4 μg/L) larger than for the prednisolone group (n = 15). The average decrease in CAI was 1.9 points (95% CI, −2.7 to −1.2) larger for the prednisolone group than for the control group and 1.2 points (95% CI, −2.1 to −0.4) larger than for the cyclosporine group. Conclusions Over a 3‐week treatment period, cats with presumed chronic pancreatitis that received cyclosporine had a larger decrease in serum fPLI concentration compared with cats that were treated with an immunosuppressive dosage of prednisolone or cats that received only symptomatic treatments. However, clinical improvement was more apparent with prednisolone, but not cyclosporine.